Use of Methotrexate in the Treatment of Moderate to Severe Plaque Psoriasis in France: A Practice Survey - Fougerousse AC; Mery-Bossard L; Parier J; Taieb C; Bertolotti A; Maccari F (Dove Medical Press, 2021)
Anne-Claire Fougerousse,1 Laure Mery-Bossard,2 Josiane Parier,3 Charles Taieb,4 Antoine Bertolotti,5,6 Francois Maccari3 On behalf of GEM ResoPso1Dermatology Department, Hôpital d’Instruction des Armées Bégin, Saint Mandé, 94160, France; 2Dermatology Department, Centre Hospitalier Intercommunal Poissy Sant Germain en Laye, Saint-Germain-en-Laye, 78100, France; 3Private Practice, La Varenne Saint Hilaire, Saint-Maur-des-Fossés, 94210, France; 4European Market Maintenance Assessment, Patients Priority Department, Fontenay sous-Bois, France; 5Infectious Diseases and Dermatology Department, Centre Hospitalier Universitaire de la Réunion, Saint Pierre, La Réunion, France; 6Inserm CIC1410, Centre Hospitalier Universitaire de la Réunion, Saint Pierre, La Réunion, FranceCorrespondence: Anne-Claire FougerousseDermatology Department, Hôpital d’Instruction des Armées Bégin, 69 Avenue de Paris, Saint Mandé, 94160, FranceTel + 331 43 98 50 00Fax + 331 43 98 49 15Email ac.fougerousse@gmail.comPurpose: To evaluate the modalities of methotrexate prescription for moderate to severe psoriasis by dermatologists in France.Patients and Methods: We performed a national online practice survey between October and December 2020.Results: A total of 254 dermatologists responded, 237 reported prescribing methotrexate for moderate to severe psoriasis in adults, of which 57% as a first line systemic treatment. Nineteen percent reported performing a test dose at the initiation of treatment. Methotrexate was prescribed orally in 54.7% of cases, subcutaneously in 44.8% of cases and intramuscularly in 0.4% of cases. The initial weekly dose of methotrexate was < 15 mg for 30% of the dermatologists and ≥ 15 mg for 70% of them. Two hundred and three dermatologists had already change the route of administration for methotrexate from the oral to injectable form due to poor tolerance (48.3%), lack of efficacy (35%) or lack of compliance (16.7%). Two hundred thirty-four dermatologists (98.7%) reported prescribing folic acid with methotrexate, and 79.3% reported prescribing tests evaluating the risk of hepatic fibrosis. Forty-three percent of dermatologists have not initiated or have reduced their prescriptions since the beginning of the pandemic of COVID-19. Prescribing patterns were different according to the type of practice (private practice versus hospital/mixed practice).Conclusion: Methotrexate is used by the majority of dermatologists interviewed for moderate to severe psoriasis in adults, with heterogeneity of practices.Keywords: psoriasis, methotrexate, practice survey, dermatologists